EXTRACELLULAR MATRIX OF DECELLULARIZED BOVINE OVARIES AS A NOVEL BIOMATERIAL FOR IN VITRO RECONSTRUCTION OF THE OVARIAN MICROENVIRONMENT (CIPEEX, 2025)
Reproductive tissue bioengineering has made significant progress, opening new perspectives for the development of treatments for patients with reproductive disorders. Various innovative techniques have been explored to fabricate biomaterials that enable the cultivation of different cell types, with the aim of studying gametogenesis and promoting differentiation into germ cells. Among these techniques, decellularization stands out due to its ability to remove cells from the extracellular matrix while preserving its biological function, biochemical composition, and three-dimensional structure. This study aimed to develop a methodology for the decellularization of whole bovine ovaries using a constant perfusion technique via the ovarian artery. The ovaries were subjected to a decellularization protocol with a 0.5% SDS solution for 48 hours. This method proved to be effective in completely removing cellular components while preserving both the macrostructure and microstructure of the native tissue. To assess the integrity of the extracellular matrix after decellularization, histological analyses, scanning electron microscopy (SEM), and DAPI staining were performed. The partial results indicate that the established protocol successfully promoted efficient decellularization while maintaining the structural and functional characteristics of the extracellular matrix. In vitro assays demonstrated that the resulting scaffolds allowed for cell adhesion and proliferation, suggesting that the developed methodology holds great potential for the production of ovarian scaffolds with possible future applications in reproductive bioengineering and regenerative medicine. We conclude that the arterial perfusion-based decellularization method developed in this study is highly effective in producing decellularized ovarian scaffolds, preserving both the structural integrity and biochemical properties of the extracellular matrix. These scaffolds present themselves as a promising platform for in vitro studies of cell adhesion and proliferation, with significant potential for applications in reproductive bioengineering therapies and regenerative medicine.
Keywords: decellularization; reproductive bioengineering; ovarian scaffolds